1979
DOI: 10.1152/physrev.1979.59.3.527
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxide metabolism in mammalian organs.

Abstract: I. INTRODUCTION AND HISTORICAL BACKGROUND The existence of significant levels of potentially dangerous oxidants in cells and tissues under physiological conditions has frequently been proposed but had previously received little quantitative support. Current approaches to the direct 0031~9333/7%WOOOO~Ol.25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

69
2,663
5
77

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 5,307 publications
(2,814 citation statements)
references
References 56 publications
69
2,663
5
77
Order By: Relevance
“…Both NADH-ubiquinone reductase and ubiquinone-cytochrome c reductase generate O~ and H202 (6). Because the transition from a twoelectron (NADH and FADH2) to a one-electron (ubiquinone) transfer involves the formation of semiubiquinone (QH~ this segment of the ETC becomes a primary site for O~ production (6).…”
Section: Mitochondrial Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Both NADH-ubiquinone reductase and ubiquinone-cytochrome c reductase generate O~ and H202 (6). Because the transition from a twoelectron (NADH and FADH2) to a one-electron (ubiquinone) transfer involves the formation of semiubiquinone (QH~ this segment of the ETC becomes a primary site for O~ production (6).…”
Section: Mitochondrial Theorymentioning
confidence: 99%
“…A metal-catalyzed Fenton reaction or HaberWeiss reaction between O~ and H202 may give rise to "OH (1). Liver mitochondria is estimated to produce 24 nmol O~ rain per g of tissue; with an active conversion to H202 by SOD, a steady-state O~ concentration of 8x10 .8 M can be derived (6). Heart mitochondria generate 0.3-0.6 nmol/min per mg protein representing 2% of the tissue's total oxygen consumption.…”
Section: Mitochondrial Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The production of mdROS was modeled as a fraction, or shunt , of electrons from the electron transport chain into the matrix, as previously described 5, 47, 51, 52. Studies have shown that under physiological conditions, up to 2% of the electron flowing the respiratory chain are partially reduced to form the superoxide,53 thus the physiological value of shunt was set as 2%. Pathological shunt was set as 10% or 14% to induce sustained mitochondrial oscillations, which is consistent with our previous computational studies 5, 47, 52.…”
Section: Methodsmentioning
confidence: 99%